ASSESSMENT OF MAIZE GRAIN QUALITY BY DNA MARKERS - Prysiazhniuk L. M.,; Honcharov Yu. O.,; Shytikova Yu. V.,; Melnyk S. I., (Scientific Journal of Pedagogy and Economics, 2021)
To evaluate maize lines on the basis of the high content of lysine and tryptophan and waxiness using SSR markers.